Konsumsi Energi Menggunakan Protokol Routing Temporally Ordered Routing Algorithm (TORA) Pada Jaringan Mobile Ad-Hoc Network (MANET) - Sandy Prasetyo; Primantara Hari Trisnawan; Fariz Andri Bakhtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Self-configure is unique to the MANET network, where the network is formed from independent nodes that communicate each other. In MANET, there is a standardized route determination mechanism in sending data packets called the routing protocol. Nodes in a MANET network require energy to communicate, while energy on nodes is limited. Therefore, when testing the network performance, energy consumption is a factor that needs to be taken into account. Temporally Ordered Routing Algorithm (TORA) is a routing protocol that can operate on MANET networks. This study aims to calculate the energy consumption of the MANET network by implementing the TORA protocol. The simulation is carried out with a scenario of increasing the number of nodes from 30, 50 to 70 in an area of ​​1000m x 1000m with an initial energy of 1000 Joules and a simulation time of 100 seconds. This scenario is performed on two different mobility models, namely the fixed grid model and the random waypoint model. From the simulation data, the average value of energy consumption in the fixed grid model for 30 nodes is 65.374 Joule, 50 nodes are 62.262 Joules and 70 nodes are 61.549 Joules. Whereas the random waypoint model for 30 nodes is 62.807 Joules, 50 nodes are 55.808 Joules and 70 nodes are 54.388 Joules. With the scenario of increasing the number of nodes there is a decrease in the average value of energy consumption in the two mobility models, this is due to the multi-route mechanism in the TORA.